"Global capital, National State and the politics of money / edited by Bonefeld Werner and Holloway" - "Werner, Bonefeld (ed.)" (London, 1996)
The politics of international debt have received increasing attention in recent years. However, discussion of the politics of money has focused on Latin American and 'third' world countries. So far there has been little treatment of the politics of scarce money and of money as a political category in relation to 'advanced' countries. The central theme of the book is the limitations and constraints on state action which arise from the relation between the (nation) state and the global flow of money.
Keywords: Capital